(untitled) (Polish Yearbook of International Law, 2021)
This article discusses the development of international law concerning the underwater cultural heritage (UCH), with particular emphasis on the 2001 UNESCO Convention on the subject. It attempts to set out the main legal solutions adopted in the 2001 Convention. However, in order to achieve this aim, it traces the genesis of the Convention and identifies the problems which prompted UNESCO to initiate the negotiations that ultimately led to the adoption of the 2001 Convention. Hence, before analysis of the UNESCO treaty it firstly describes the initial phase of the development of law regarding UCH, which was mostly based on the national laws of particular coastal States, as well as in some instances on the laws of salvage. Subsequently, the article turns to the discussion concerning the (in)famous two provisions of the UN Convention on the Law of the Sea (UNCLOS) dealing with archaeological objects, as well as the efforts that were undertaken within the framework of the Council of Europe to adopt a convention on UCH.